Production and Partial Purification of Alpha Amylase from Bacillus subtilis (MTCC 121) Using Solid State Fermentation - Dibyangana Raul; Tania Biswas; Suchita Mukhopadhyay; Shrayan Kumar Das; Suvroma Gupta (Biochemistry Research International)
Amylase is an enzyme that catalyzes the breakdown of starch into sugars and plays a pivotal role in a variety of areas like use as digestives, for the production of ethanol and high fructose corn syrup, detergents, desiring of textiles, modified starches, hydrolysis of oil-field drilling fluids, and paper recycling. In the present work, solid state fermentation (SSF) for α-amylase production has been used in lieu of submerged fermentation (SmF) due to its simple technique, low capital investment, lower levels of catabolite repression, and better product recovery. Bacillus subtilis has been well known as producer of alpha amylase and was tested using solid state fermentation for 48 hours at 37°C with wheat bran as substrate. Comparison between different fermentation hours demonstrated high yield of alpha amylase after 48 hours. This alpha amylase has optimum pH and temperature at 7.1 and 40°C, respectively. With the goal to purify alpha amylase, 30–70% (NH4)2SO4 cut concentrated the amylase activity threefold with respect to crude fermented extract. This was verified in quantitative DNS assay method as well as in zymogram gel profile. The exact molecular weight of the amylase is yet to be determined with the aid of other protein purification techniques.